Pengaruh Trading Volume Activity, Pengumuman Stock Split dan Volatilitas Saham terhadap Actual Return - Rizka Azzahrah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The goal of this study is to discover how stock split announcements and stock volatility affect actual stock returns when trading volume activity (TVA) is used as an intermediary variable. All registered firms on the Indonesia Stock Exchange that implemented a stock split policy in the period of 2015 to 2020 were included in the experiment's population. The 33 samples of companies were obtained as samples in the study using the purposive sampling method. To evaluate the intervening factors, the hypothesis was examined using multiple linear regression models and path analysis. Stock splits and TVA had no effect on actual stock returns, but stock volatility did. Stock splits have a large beneficial effect on TVA, whereas stock volatility has little effect. The TVA cannot be used as a moderator in the relationship between stock split and volatility on actual return. Other variables, such as stock volatility and TVA, are purposed to be included by future researchers in order to better clarify the stock return variable as a whole.